Morphofunctional anatomy, swimming behavior and conservation of Corydoradine species from Northwestern La Plata basin - Felipe Alonso; Guillermo Enrique Terán; Gaston Aguilera; Wilson Sebastián Serra Alanis; Juan Marcos Mirande (Acta Zoológica Lilloana)
This study focuses on endemic Corydoradinae species from the northwestern La Plata River basin, specifically Urkumayu micracanthus, Urkumayu gladysae, Urkumayu petracinii, and Hoplisoma osvaldoi, inhabiting piedmont high-altitude, fast-flowing Andean rivers. Using direct behavioral observations and morphometric analyses, we characterized their swimming behavior and its relationship to the morphology and their habitat conditions characterized by intense seasonal flooding during the summer. The findings reveal that Corydoradinae from these environments exhibit unique swimming behaviors, such as energy-efficient tripod-like resting postures, driven by negative buoyancy and streamlined body shapes. Morphological traits such as reduced pectoral and dorsal-fin spines and lower body depth enhance hydrodynamic efficiency. Comparisons with congeners from low-flow environments highlight evolutionary convergence within the species from different lineages. Conservation assessments reveal significant threats to these species, including habitat degradation, pollution, and anthropogenic disturbances, particularly for U. petracinii and U. gladysae, which are classified as Critically Endangered. This study underscores the critical importance of conserving these ecosystems, providing insights into the interplay between morphology, behavior, and environmental pressures, and advancing our understanding of species diversification in Neotropical freshwater ecosystems.